Investigation of the effects of water injection into an SI engine running on M15 methanol fuel on engine performance and exhaust emissions. (15th December 2022) - Cesur, Idris
Abstract: The use of alternative fuels is an effective method to reduce pollutant emissions from spark-ignition engines. However, the usage of alternative fuels alone will not be adequate comply with strict emission standards. Water injection is one of the measures taken during combustion to achieve the desired emission values. However, deterioration in engine performance, which is not desired, occurs with the measures taken. In this study, a gasoline-methanol blend (85% gasoline + 15% methanol) was used as a fuel in a spark-ignition engine. Water was injected into the intake manifold at different rates to reduce emissions further and improve engine performance in an engine running on M15 fuel. Water was injected into the intake air with an electronic control system with 10, 20, and 30% mass ratios of the engine fuel consumption. As a result of the experimental studies conducted under full load conditions, it was determined that the effective power decreased by 2.5%, and the specific fuel consumption increased by 3.5% compared to the standard condition in the engine fueled with M15. It was revealed that there was a 6% decrease in HC emission at 2200 rpm and a 4% decrease in NOx emissions at 2600 rpm. In comparison to standard engine data, when water injection was applied to the engine, there was a decrease up to 16% in HC emissions and up to 12% in NOx emissions. In comparison to the standard data, an increase of 2.5% in the effective power was observed with 20% water injection in the effective power. Highlights: The use of alternative fuels is an effective method to reduce pollutant emissions from SI engines. The water injection method improves the emission and performance parameters to the engines. NOx emissions significantly have decreased with the water injection method. Performance and specific fuel consumption are improved with water injection method.